PINK1 antagonize intracerebral hemorrhage by promoting mitochondrial autophagy. Issue 10 (28th August 2021) - Li, Jingchen; Wu, Xiaoyun; He, Yanbo; Wu, Song; Guo, Erkun; Feng, Yan; Yang, Jipeng; Li, Jianliang
Abstract: Background: Intracerebral hemorrhage (ICH) causes neurotransmitter release, oligemia, membrane depolarization, mitochondrial dysfunction, and results in the high rate of mortality and functional disability. Here, we focus on PTEN‐induced kinase 1 (PINK1), a mitochondrial‐targeted protein kinase, and explore its role in ICH progression. Methods: The qPCR and Western blot were performed to examine the expression of PINK1 in ICH patients and mouse model. PINK1 gain‐ and loss‐of‐function mice were used to evaluate their protective role on brain injury and behavioral disorders. Flow cytometry was carried out, mitochondrial membrane potential and reactive oxygen species production were detected to explore the distribution and neuroprotective function of PINK1. Results: PINK1 mRNA was upregulated, however, its protein was downregulated in ICH patients. The reduction of PINK1 was mainly happened in microglial cells in ICH model. Overexpression of PINK1 is able to rescue ICH‐induced behavioral disorders. PINK1 protects ICH‐induced brain injury by promoting mitochondrial autophagy in microglia. Conclusion: PINK1 possesses a neuroprotective role and antagonizes ICH by promoting mitochondrial autophagy, which may be of value as a therapeutic target for ICH treatment.